EVOLUTION OF COMPETITION LAW IN SERBIA - Spasić, Ivanka (Law - Theory and Practice, 2010)
Discussing the evolution of competititon law in Serbia we have primarily in mind a few basic questions of competition and a few competition acts. The basic questions of competition in Serbia are identical with the basic competition problems in EU and european countries, and they are focused on the acts threatening the competioton (restrictive agreements, abuse of dominant position and making of concentrations-mergers) and the problems of functioning of the protection of competition. Concerning the acts, first of all we must mention the Antimonopoly law than the Law on protection of competition from 2005, and the law with the identical name from 2009. The Antimonopoly law is the „early history“ of Serbian competition law , but the Law on protection of competition from 2005 is very importante because it“ s regulations established foundamental competition institutes in Serbia. The basic questions of competition (restrictive agreement, abuse of dominant position, and concentrations) are well done, and the mood of their regulation is good; just the contrary the moode of the protection had shown many difficulties. This difficulties are the main cause that the new act on protection of competititon has been introduced (2009). The new Law on protection of competititon regulate the „protection part“ much beter than the former one. Comission for the protection of competititon has now more rights and possibilities to perform the protection of the competititon.